RELATIONSHIP OF GROWTH HORMONE GENE WITH SOME OF PRODUCTIVE TRAITS OF COMMON CARP Cyprinus carpio.L - & Al-Khshali, AL-Azzawy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was carried out at Al-Radhwaniyah fish Reservoir (Baghdad) to investigate the polymorphism of GH gene and relationship with some of productive characteristics (total weight gain (T.W.G), daily growth rate (D.G.R), relative growth rate (R.G.R) and specific growth rate (S.G.R) in common carp. single nucleotide polymorphism (SNPs) in GH gene was analyzed by direct sequencing. Two SNP were identified in the third intron of GH1, the first SNP at site A1132T was negative correlated with growth traits, AA Genotype (wild)  was significant(p